Mitochondrial Complex I Core Protein Regulates cAMP Signaling via Phosphodiesterase Pde2 and NAD Homeostasis in Candida albicans - She, Xiaodong; Zhang, Lulu; Peng, Jingwen; Zhang, Jingyun; Li, Hongbin; Zhang, Pengyi; Calderone, Richard; Liu, Weida; Li, Dongmei (Frontiers in Microbiology, 2020)
The cyclic adenosine 3′,5′-monophosphate (cAMP)/protein kinase A (PKA) pathway of Candida albicans responds to nutrient availability to coordinate a series of cellular processes for its replication and survival. The elevation of cAMP for PKA signaling must be both transitory and tightly regulated. Otherwise, any abnormal cAMP/PKA pathway would disrupt metabolic potential and ergosterol synthesis and promote a stress response. One possible mechanism for controlling cAMP levels is direct induction of the phosphodiesterase PDE2 gene by cAMP itself. Our earlier studies have shown that most single-gene-deletion mutants of the mitochondrial electron transport chain (ETC) complex I (CI) are hypersensitive to fluconazole. To understand the fluconazole hypersensitivity observed in these mutants, we focused upon the cAMP/PKA-mediated ergosterol synthesis in CI mutants. Two groups of the ETC mutants were used in this study. Group I includes CI mutants. Group II is composed of CIII and CIV mutants; group II mutants are known to have greater respiratory loss. All mutants are not identical in cAMP/PKA-mediated ergosterol response. We found that ergosterol levels are decreased by 47.3% in the ndh51Δ (CI core subunit mutant) and by 23.5% in goa1Δ (CI regulator mutant). Both mutants exhibited a greater reduction of cAMP and excessive trehalose production compared with other mutants. Despite the normal cAMP level, ergosterol content decreased by 33.0% in the CIII mutant qce1Δ as well, thereby displaying a cAMP/PKA-independent ergosterol response. While the two CI mutants have some unique cAMP/PKA-mediated ergosterol responses, we found that the degree of cAMP reduction correlates linearly with a decrease in total nicotinamide adenine dinucleotide (NAD) levels in all mutants, particularly in the seven CI mutants. A mechanism study demonstrates that overactive PDE2 and cPDE activity must be the cause of the suppressive cAMP-mediated ergosterol response in the ndh51Δ and goa1Δ. While the purpose of this study is to understand the impact of ETC proteins on pathogenesis-associated cellular events, our results reveal the importance of Ndh51p in the regulation of the cAMP/PKA pathway through Pde2p inhibition in normal physiological environments. As a direct link between Ndh51p and Pde2p remains elusive, we suggest that Ndh51p participates in NAD homeostasis that might regulate Pde2p activity for the optimal cAMP pathway state.